Smokers' perceptions of risks and harm from snus relative to cigarettes: A latent profile analysis study. (April 2019) - Wackowski, Olivia A.; Ray, Anne E.; Stapleton, Jerod L.
Abstract: Introduction: Certain types of smokeless tobacco (SLT) products, particularly snus, carry fewer health risks than cigarette smoking and might be able to serve as harm-reduction products for smokers. However, studies frequently find that smokers misperceive SLT and snus to be as or more harmful than smoking. This perception is often measured with a single general harm question, and research on underlying risk perceptions is limited. Methods: Using a sample of 256 current smokers, we utilized Latent Profile Analysis to examine response profiles to items that assessed perceived risk of specific health outcomes (lung cancer, heart disease, oral cancer) from snus relative to cigarettes, along with the typical single item measure of overall harm from snus compared to cigarettes. Results: Three smoker response profiles emerged. Almost half (44.9%) of smokers perceived snus to be as or more risky than cigarettes for all three specific health outcomes (group 1), while over one third (38.3%) had an elevated perceived risk for oral cancer only (group 2). About 17% of smokers perceived snus to have lower risks for lung cancer only (group 3). Across each profile, perceived risk was highest for oral cancer. Conclusions: If smokers are to consider snus for harm-reduction, efforts may be needed to better inform smokers about their lower relative risks, including for particular health outcomes of interest. This study also suggests that smokers may vary in their level of need for information to correct their relative risk misperceptions. Highlights: Three distinct subgroups related to perceptions of harm and risk from snus use relative to cigarette smoking were identified. 45% of participants perceived snus to be as harmful/risky as cigarettes across all indicators (labeled "non-discerners"). 38% perceived snus to pose less risk for lung cancer and heart disease than cigarettes, but the same risk as cigarettes for oral cancer. 16.8% were accurate in their perceptions related to lung cancer, but not with regards to heart disease and oral cancer. Across all profiles, perceived risk was highest for oral cancer.